If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -6 = 4x Reorder the terms: -6 + 7y = 4x Solving -6 + 7y = 4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 7y = 6 + 4x Combine like terms: -6 + 6 = 0 0 + 7y = 6 + 4x 7y = 6 + 4x Divide each side by '7'. y = 0.8571428571 + 0.5714285714x Simplifying y = 0.8571428571 + 0.5714285714x
| 6-7(3x-5)=104 | | 3x+13=4x+19 | | 3.2b+-5.7=20.1 | | 4/100-5700/x | | 114/(-3)= | | 3-4g=15 | | .5x=5000+300 | | 30(47+2)=7 | | 4/100=5000/x | | (4x/5y^4)2 | | .5x-300=5000 | | 3x+5=45-3x | | 6(b+-2.4)=7.6 | | 4=-2+20 | | 0.75b+-0.35=6.35 | | 6x-3=13x-3 | | 15=3y-8 | | 32=x-6 | | l=5400+300n-50n^2 | | Y=0.3(25.4)+7 | | 8x/x-6=0 | | 15=0.3x+7 | | c=7/3(k-88) | | 2x(x-6)=x-20 | | 11-2(s-5)= | | F(x)=2x^4-5x^3-x+14 | | 6f=28+7 | | 85=3x-200 | | y=9+sinx | | x^2+6x-60=75 | | 8x-4/2 | | -8[6-8]= |